Detecting the upturn of the solar 8B neutrino spectrum with LENA - R. Möllenberg; F. von Feilitzsch; D. Hellgartner; L. Oberauer; M. Tippmann; J. Winter; M. Wurm; V. Zimmer (Physics Letters B, 2014)
LENA (Low Energy Neutrino Astronomy) has been proposed as a next generation 50 kt liquid scintillator detector. The large target mass allows a high precision measurement of the solar 8B neutrino spectrum, with an unprecedented energy threshold of 2 MeV. Hence, it can probe the MSW-LMA prediction for the electron neutrino survival probability in the transition region between vacuum and matter-dominated neutrino oscillations. Based on Monte Carlo simulations of the solar neutrino and the corresponding background spectra, it was found that the predicted upturn of the solar 8B neutrino spectrum can be detected with 5σ significance after 5 years.